1905
DOI: 10.1021/ja01987a006
|View full text |Cite
|
Sign up to set email alerts
|

ADRENALIN, THE ACTIVE PRINCIPLE OF THE SUPRARENAL GLANDS.*

Abstract: THE OBJECT of this paper is to take up the chemical side of adrenalin, the active principle of the suprarenal glands, but, before doing so, I will review very briefly this subject up until the time when adrenalin was discorered. Addisonlt (1855) was the first to recognize the great importance of the suprarenal glands in the animal economy, particularly in their relation to the disease since called "Addison's Disease." Vulpian2 (1856) observed that the expressed juice of these glands, obtained from various anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1910
1910
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…At an intermediate pH (6)(7)(8) adrenaline in aqueous buffer is oxidized to red substances; the speed of the reaction and the nature of the final products are dependent on the catalysts and buffers employed. Neutral solutions of adrenaline in the complete absence of traces of heavy metals probably do not undergo autoxidation at any appreciable rate (c/.…”
Section: Catalytic Oxidation At Intermediate Ph'smentioning
confidence: 99%
See 2 more Smart Citations
“…At an intermediate pH (6)(7)(8) adrenaline in aqueous buffer is oxidized to red substances; the speed of the reaction and the nature of the final products are dependent on the catalysts and buffers employed. Neutral solutions of adrenaline in the complete absence of traces of heavy metals probably do not undergo autoxidation at any appreciable rate (c/.…”
Section: Catalytic Oxidation At Intermediate Ph'smentioning
confidence: 99%
“…The development of characteristic colors during the oxidation of aqueous extracts of mammalian suprarenal capsules was first observed over a century ago. In 1856 Vulpian reported that (a) on standing in air, the extract soon became rose-carmine in color, (6) the colors could also be produced by the action of certain oxidizing agents, and (c) although small quantities of alkali facilitated the reaction, larger quantities apparently hindered it (258, 259). It was nearly forty years after these observations were made that the powerful physiological activity of the extracts was first demonstrated (188).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not until 1958 that a purely chemical determination of the exact stereochemic configuration of ( -)-adrenaline was done (Pratesi 1958). Aldrich (1905) discussed the empirical and structural formulas of that time and summarized the historical evolution of adrenaline. Aldrich stated that the interest in adrenaline, or more correctly the adrenal medullary extract, had accelerated greatly from the forty-year period of 1855-1895, where only ten articles on the subject had been published, to the decade of 1895-1 905, where more than 30 articles were published.…”
Section: The Chemistry Of Adrenalinementioning
confidence: 99%
“…The progress in the field of adrenergic drugs started with the elucidation of the structure of epinephrine (I) (1) and its synthesis (2,3). Intensive pharmacological investigations thereafter were conducted and a great number of related amines were prepared and tested in an effort to correlate chemical structure to biological activity (4)(5)(6).…”
mentioning
confidence: 99%